Bolesław Lewański (1881-1952) - „malarz rzeczywistości i baśni”? (Kronika Bydgoska, 2016)
Bolesław Lewański graduated from the Berlin School of Fine Arts (Berliner Kunstschule) in 1905. He completed his art education in Munich and Paris. At first, he was connected with the artistic community of Poznań. In 1920, Lewański settled permanently in Bydgoszcz. Starting from the early 1920’s, he actively participated in the artistic life of Bydgoszcz, becoming involved in organising the State School of Art Industry (1920-1923) and the Zachęta Fine Arts Association (1921-1923). After liquidation of the school in 1923, Lewański stayed in Bydgoszcz and worked as a drawing teacher at the State Classical Grammar School. The Bydgoszcz stage of his creative works includes the controversial painting The Sacred Heart designed for the high altar of the Sacred Heart Church. Of particular importance to familiarisation with the paintings of Lewański are two exhibitions presented at the Bydgoszcz Municipal Museum in 1926 and 1933. Zygmunt Malewski named Lewański ”a painter of reality and fairy-tales”. He identified two principal thematic trends dominant in his paintings. Landscapes and genre scenes from Polesie, Wielkopolska and Pomerania, and portraits are the first one. The second trend includes symbolic-metaphorical paintings and works inspired by mythology, legends and fairy-tales, often referring to the Slavonic beliefs and traditions. The artist’s works include an interesting thread of ecclesiastic painting, where religious plots are the basic topic of composition, e.g. the composition entitled Autumn - decease (1922) and a famous painting frequently reproduced depicting Our Lady with the Child Jesus in a landscape. The artist created innovative thematic depictions set in the reality of the local landscape, folklore.